2022
DOI: 10.1155/2022/6602899
|View full text |Cite|
|
Sign up to set email alerts
|

On Acyclic Structures with Greatest First Gourava Invariant

Abstract: Let ξ be a simple connected graph. The first Gourava index of graph ξ is defined as G O 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Wang et al [17] obtained the maximum value of the Gourava indices for trees with given independence numbers. Mariam et al [18] provided an upper bound for the first Gourava index of trees with a given order, size, diameter, and pendant vertices. Basavanagoud et al [19,20] determined the Gourava and hyper-Gourava indices of cactus chains and suggested the applications of Gourava indices to the octane isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [17] obtained the maximum value of the Gourava indices for trees with given independence numbers. Mariam et al [18] provided an upper bound for the first Gourava index of trees with a given order, size, diameter, and pendant vertices. Basavanagoud et al [19,20] determined the Gourava and hyper-Gourava indices of cactus chains and suggested the applications of Gourava indices to the octane isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%